Terapia por ondas de choque associada ao fortalecimento excêntrico versus fortalecimento excêntrico isolado no tratamento das tendinopatias insercionais do Aquiles: ensaio clínico randomizado. - Mansur, Nacime Salomao Barbachan [UNIFESP] (2019)
Background: There is no consensus for the treatment of Achilles insertional tendinopathy (AIT). The eccentric exercises protocol (EE) and the shockwave therapy (SWT) persists as options in the clinical management of this condition, despite its inconclusive results. Objective: To evaluate the effectiveness of SWT adjuvant to EE as compared to EE with placebo in the AIT treatment, considering function. Method: Ninety-seven patients diagnosed with AIT were randomly allocated into two groups. Those inserted in the intervention group (SWT) received three sessions of radial shockwaves (2000 to 3000 impulses, 7 to 10 Hz and 1.5 to 2.5 bars) and the 12-week EE protocol for the calcaneal tendon. Those destined to the control group (CON) received the same 12 weeks of EE and SWT simulations (sham). Patients were followed up to 24 weeks after treatment initiation. The primary assessment was the tendon function by the VISA-A score. For the secondary, pain by the VAS, algometry, foot function by the AOFAS and FAOS scores and quality of life by the SF-12 were collected. Results: The two groups, despite the positive evolution with the treatments within the study period, showed no differences (p<0,05) in any of the analyzed variables. Conclusion: Extracorporeal shockwave therapy does not potentialize the effects of the eccentric strengthening in the Achilles insertional tendinopathy treatment.